Maintaining Integrity and Expanding Authority: The Role of Ulama Women in Madura - Zain , Naura Safira Salsabila; Anoraga , Bhirawa; Irsyadulhaq , Irsyadulhaq (LPPPM STAI Darul Hikmah Bangkalan, 2023)
In Indonesia, religious authorities are viewed as one of the most influential figures due to the number of pesantren alumni who play important roles in society. As in Madura, religious authorities are the obvious figures within the puritanical, conservative community with a strong religious attachment community. Meanwhile, Ulama women are viewed to have a limited role due to the adoption of patriarchal culture in Madura. In fact, in this modern era, there has been an important transformation done by Ulama women in strategizing daÊ¿wa to significantly influence the ummah, which will be discussed in this research. This paper will first elaborate on the social background, the authority of religious figures, and the roles of women in Madura to broadly observe the role of Ulama women in maintaining their integrity and expanding their authority. The methodology applied in this research is qualitative, with a study case approach in Sampang, Madura. Data are collected from interviews as primary sources and articles related to the topic from books, journals, and documents as secondary sources. The framework used in the research is the concept of new Muslim womanhood in assessing the transformation to increase the reliability and validity of the research.